Study of the Properties and Features of the Composition of the Oils of the Northern Territories of Western Siberia; AIP Conference Proceedings; Vol. 2167 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2019 (AMHS'19) - Krasnoyarova N. A. Nataliya Alekseevna; Chuykina D. I. Darya; Serebrennikova O. V. Olga Viktorovna; Dorofeeva N. V. Nataliya Valerjevna (2019, 2019)
Title screen